LEFLUNOMIDE USE IN THE PROPHYLACTIC TREATMENT OF GOUT - Gezmiş Kimyon (Rheumatology Quarterly)
Gout is one of the most common inflammatory arthritides and is under-treated despite effective treatment options. Colchicine, non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids (CSs) are usually used for prophylactic treatment. Drugs used in prophylactic treatment may have some limitations. Colchicine, the most commonly used agent in prophylactic treatment, has a low level of evidence, while NSAIDs and CSs, which are recommended when colchicine cannot be used, have a very low level of evidence. There are unmet needs in the prophylactic treatment of gout. Our patient, a 69-year-old man, had his first episode of arthritis 19 years ago in the first metatarsophalangeal joint. The patient presented with classic gout attacks and no additional rheumatic disease findings. However, he could not use allopurinol and febuxostat, which are urate-lowering treatments; or colchicine, CSs, and NSAIDs used in prophylactic treatment, for various reasons. In the 12th year of the disease, he had an arthritis attack in his wrist. No gout attacks were detected for a long time after starting leflunomide (LEF). LEF appears effective for the treatment of some patients.